On the Edge between Manuscript and Oral Text: some Methodological Conundrum - Subačius, Paulius V. (Senoji Lietuvos literatūra, 2015)
Up until recently the sermon was one of the dominant genres of public texts. However, in contemporary publications of sermons it is not easy to trace the authentic shape of these texts. Sermons dedicated to the same occasion or liturgical festivity sometimes have more textual coincidences than differences, thus the selection criteria and the inclusion of the demonstrated variations become particularly urgent problems. Question arises whether it is possible to write universal commentaries on sermons, which would be equally suitable for the readers brought up in a Christian environment and those totally ignorant of religious practice. These issues are discussed in the paper while referring to a collection of manuscript notes of sermons by the Lithuanian poet and wellknown preacher Silvestras Gimžauskas from the second half of the nineteenth century and its critical edition.
Keywords: -